PENGARUH FITUR APLIKASI BLACKBERRY MESSENGER (BBM) PADA ANDROID DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE BERBASIS ANDROID - MOHAMMAD FIKRI AMRULLAH (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2018)
This research aims to identify the factors that influence the purchase decision based on Android Smartphone Students study at Muhammadiyah University of Gresik . This study used a sample of 80 respondents , the type of data used primer.Experiance also test two independent variables , namely fuel and Lifestyle Features that affect the purchase decision . The purpose of this study presented was to determine the effect of lifestyle features and the purchase intention android based smartphone by using linear regression analysis bergand . The results showed that the fuel features significantly influence the purchase decision android based smartphone